Seminar-Challenges and Opportunities in Horticulture in Collaboration with International Conference on Horticulture (ICH-2009) Horticulture for Livelihood Security and Economic Growth - Planning Commission (Planning Commission, 2009)
The International Conference on Horticulture (ICH-2009) with the theme Horticulture for Livelihood Security and Economic Growth was held in Bangalore, Karnataka State, India during November 9-12, 2009. It was organized by Dr. Prem Nath Agricultural Science Foundation (PNASF), Bangalore in association with Vegetable Science International Network (VEGINET), Bangalore and University of Agricultural Sciences (UAS), Bangalore in collaboration with national and international organizations like, Indian Council of Agriculture Research (ICAR), New Delhi; Ministry of Agriculture and Cooperation, Government of India; Planning Commission, Government of India; National Horticulture Mission, New Delhi; Karnataka Department of Horticulture; FAO, Rome; International Crops Research Institute for the Semi-Arid Tropics (ICRISAT), India; International Center for Agricultural Research in the Dry Areas (ICARDA), Syria; AVRDC - The World Vegetable Center, Taiwan; International Center for Underutilized Crops (ICUC), Sri Lanka and others.
Planning Commission, Government of India
Planning Commission, Government of India